Pendekatan Tringo dengan Strategi TPACK untuk Mewujudkan Pembelajaran Inovatif dan Berkelanjutan di Era Digital - Fitri, Karina Rahmah; Kuswandi, Dedi; Fadli, Muhibuddin (Universitas Pahlawan Tuanku Tambusai, 2025)
The digital era demands innovation in learning methods that are relevant and sustainable. This study aims to evaluate the integration of the Technological Pedagogical Content Knowledge (TPACK) approach with the TRINGO strategy in the context of digital learning in Indonesia. A Systematic Literature Review (SLR) was conducted on 10 relevant studies, showing that the TPACK-TRINGO combination enhances critical thinking skills, creativity, and 21st-century competencies. Major challenges include limited technological infrastructure in remote areas, a digital literacy gap among educators, and the difficulty of adapting the TRINGO strategy within the TPACK framework. In conclusion, professional development for teachers through continuous training, infrastructure support, and cross-sectoral collaboration are critical factors in realizing meaningful and sustainable digital learning. This study contributes to the development of innovative learning models based on local values suitable for the digital era.